Стратегічні комунікації й виклики гібридної війни: українські реалії - Зикун, Наталія Іванівна (ТНУ ім. В. І. Вернадського, 2018)
Узагальнюються наукові підходи до визначення поняття стратегічних комунікацій. Аналізуються ключові проблеми формування системи стратегічних комунікацій в Україні. Визначаються завдання розвитку окремих її елементів, зокрема, зв’язків зі ЗМІ. Обґрунтовується доцільність активізації різних рівнів системи стратегічних комунікацій (національних, регіональних, міжнародних) суб’єктами реалізації Доктрини інформаційної безпеки України, важлива роль ЗМК у досягненні загальних цілей захисту інтересів Української держави.

The article analyzes scientific approaches to the perception of the notion of strategic communications. The key problems of formation the system of strategic communications in Ukraine are analyzed. The author defines the tasks for the development of its separate elements (according to the NATO standards), in particular, liaison with mass media, the involvement of the leaders of the thought etc., that will promote the positive image of the state at the international level. The article justifies the feasibility of intensification of the different levels of the system of strategic communications (national, regional, international) by the subjects of realization of the Informational Security Doctrine of Ukraine, as well as the importance of the means of mass communication in attainment the common aims of legitimization of Ukrainian state.
Keywords: стратегічні комунікації; система стратегічних комунікацій; зв’язки зі ЗМІ; ЗМК; strategic communications; the system of strategic communications; liaison with mass media; involvement of the leaders of thought; the state image; the means of mass communication